ANALISIS KINERJA KEUANGAN PADA KIOS RANIAH - Satriani Damba; Nely Salu Padang (JURNAL ULET (Utility, Earning and Tax), 2025)
This study aims to analyze the financial performance of Kios Raniah using the profitability ratio and activity ratio measurement tools. The method used is a descriptive method with a quantitative approach. Data collection techniques use observation techniques, interview techniques and documentation. The data analysis carried out was an analysis of Kios Rania's financial statements from 2020 to 2022 using financial ratios. Based on the results of this study, it can be concluded that in terms of earning profit, reviewed from net profit in 2020 and 2021, it is classified as poor, but it has increased in 2022, so that the net profit in 2022 is quite good. In terms of asset utilization, it is reviewed in terms of inventory turnover and asset turnover from 2020 to 2022 are classified as poor.